Kontrak Perdagangan Melalui Internet (Electronic Commerce) Ditinjau Dari Hukum Perjanjian - Putu Pery Indrawan; Anak Agung Sagung Laksmi Dewi; Luh Putu Sudini (Jurnal Analogi Hukum, 2021)
Along with the development of increasingly rapid science and technology, the development of the technology includes the discovery of the internet, namely technology that allows us to exchange information with anyone and wherever the person is without being limited by space and time. The formulation of the problem in this thesis is how is the arrangement of trade contracts through the Internet (Electronic Commerce) in terms of agreement law in Indonesia? And how are the laws of the trade contract carried out through the Internet (Electronic Commerce)? In this study the research method used was a normative research method. The conclusions and suggestions from the formulation of the problem are Article 1320 of the Civil Code regulates the legal requirements of the agreement. And subjective requirements in Article 1320 BW namely the terms of agreement and the skills of the parties in the contract are not fulfilled, then one party can request that the agreement or contract can be canceled and if the objective requirement in Article 1320 BW is the existence of halal reasons not fulfilled , then the agreement or contract is canceled by law. The community to be more careful in making transactions in Electronic Commerce.